BINGKAI MEDIA ONLINE DI INDONESIA TERHADAP ATLET BERPINDAH IDENTITAS SEKSUAL - Bramantyo Utomo, Abdiel; Hasfi, Nurul; Nugroho, Adi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The issue of minorities in Indonesia is still an issue that is full of pros and cons, this is no exception for sexual minorities. The media, which has an important role to provide information to the public as a neutral party, gives a negative impression of sexual minorities. This study aims to analyse the framing done by online media in Indonesia towards athletes who change their sexual identity. Using the framing analysis method popularised by Zhongdang Pan and M. Kosicki, this research examines articles from several online media related to the Aprilia Manganang case. The results showed that online media in Indonesia tended to provide positive framing of the athlete. In addition, the majority of media framed Aprilia Manganang as a man. However, there were also some journalistic ethics violations in the reporting related to the LGBTQ coverage guidelines from the NUJ Guidlines as well as KEJ and P3SPS, such as the use of sensitive words and the selection of news topics that lead to a person's privacy area. The conclusion of this study is that not all media in Indonesia provide framing that corners sexual minorities. There are still media outlets that provide positive framing, although some violations are still found. However, the majority of violations are due to the absence of definitive guidelines in Indonesia on how to write about LGBTQ people. This research is expected to provide insight into the importance of neutrality and ethics in reporting on sexual minorities.